2022
DOI: 10.1556/2006.2022.00060
|View full text |Cite|
|
Sign up to set email alerts
|

Who feels affected by “out of control” sexual behavior? Prevalence and correlates of indicators for ICD-11 Compulsive Sexual Behavior Disorder in the German Health and Sexuality Survey (GeSiD)

Abstract: Background and aims The purpose of this study was to examine the prevalence and correlates of indicators consistent with Compulsive Sexual Behavior Disorder (CSBD)—defined and operationalized according to the ICD-11 guidelines—in a large (n = 4,633; 50.5% male; 49,5% female) probability-based German national sample. Methods Participants were asked if they had ever experienced “intense and recurring sexual impulses or sexual urges that I had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 53 publications
2
18
0
4
Order By: Relevance
“…Since the diagnostic instruments used varied remarkably in the past (from single items to elaborated questionnaires), prevalence estimates of CSBD and PPU also cover a broader range. Studies reported prevalence rates for CSBD of 4.2–7% in men and 0–5.5% in women ( Bőthe et al, 2020b ; Briken et al, 2022 ; Fuss, Briken, Stein, & Lochner, 2019 ) and similarly for PPU of 3–10% in men and from 1 to 7% in women ( Bőthe, Potenza, et al., 2020 ; Grubbs, Kraus, & Perry, 2019 ; Lewczuk, Glica, Nowakowska, Gola, & Grubbs, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the diagnostic instruments used varied remarkably in the past (from single items to elaborated questionnaires), prevalence estimates of CSBD and PPU also cover a broader range. Studies reported prevalence rates for CSBD of 4.2–7% in men and 0–5.5% in women ( Bőthe et al, 2020b ; Briken et al, 2022 ; Fuss, Briken, Stein, & Lochner, 2019 ) and similarly for PPU of 3–10% in men and from 1 to 7% in women ( Bőthe, Potenza, et al., 2020 ; Grubbs, Kraus, & Perry, 2019 ; Lewczuk, Glica, Nowakowska, Gola, & Grubbs, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…due to moral incongruence) and PPU due to behavioral dysregulation, using personcentered approaches and clinical assessments. More in-depth analyses of the complex roles that cultural values, religiosity, the content of pornography, or moral perspectives may play in diagnosing PPU are also recommended [4,5,24,93]. Furthermore, even though the results of traditional MI testing suggested the lack of potential measurement biases, and thus the adequacy of using all three scales in different populations, it should be noted that besides its strengths, this method also has its weaknesses [94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…A recent representative sample of German nationals indicated that 4.9% of men and 3.0% of women reported experiences consistent with diagnostic criteria for CSBD (Briken et al, 2022). Other nonepidemiological studies find a similar percentage of Americans report concerns about their sexual behaviors being out of control (Dickenson et al, 2018).…”
Section: Csbd Pornography and Moral Incongruencementioning
confidence: 99%